Exploring the potential of the recombinant human collagens for biomedical and clinical applications: a short review. (11th December 2020) - Chen, Zhuoyue; Fan, Daidi; Shang, Lijun
Abstract: Natural animal collagen and its recombinant collagen are favourable replacements in human tissue engineering due to their remarkable biomedical property. However, this exploitation is largely restricted due to the potential of immunogenicity and virus contamination. Exploring new ways to produce human collagen is fundamental to its biomedical and clinical application. All human fibrillar collagen molecules have three polypeptide chains constructed from a repeating Gly-Xaa-Yaa triplet, where Xaa and Yaa represent one random amino acid. Using cDNA techniques to modify several repeat sequences of the cDNA fragment, a novel human collagen, named recombinant human-like collagen (rHLC), with low immunogenicity and little risk from hidden virus can be engineered and notably tailored to speciﬁc applications. Human-like collagen (HLC) was initially used as a coating to modify the tissue engineering scaffold, and then used as the scaffold after cross-link agents were added to increase its mechanical strength. Due to its good biocompatibility, low immunogenicity, stabilised property, and the ability of mass production, HLC has been widely used in skin injury treatments, vascular scaffolds engineering, cartilage, bone defect repair, skincare, haemostatic sponge, and drug delivery, including coating with medical nanoparticles. In this review, we symmetrically reviewed the development, recent advances in design and application of HLC, and other recombinant human collagen-based biomedicine potentials. At the end, future improvements are also discussed.